2018
DOI: 10.1136/jnnp-2017-317823
|View full text |Cite
|
Sign up to set email alerts
|

A unifying theory for cognitive abnormalities in functional neurological disorders, fibromyalgia and chronic fatigue syndrome: systematic review

Abstract: BackgroundFunctional cognitive disorder (FCD) describes cognitive dysfunction in the absence of an organic cause. It is increasingly prevalent in healthcare settings yet its key neuropsychological features have not been reported in large patient cohorts. We hypothesised that cognitive profiles in fibromyalgia (FM), chronic fatigue syndrome (CFS) and functional neurological disorders (FNDs) would provide a template for characterising FCD.MethodsWe conducted a systematic review of studies with cognition-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
159
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(193 citation statements)
references
References 188 publications
(194 reference statements)
14
159
0
9
Order By: Relevance
“…Thus, our results support some previous studies that show discrepancies between subjective and objective cognitive measures in CFS (Cockshell & Mathias, 2014;Cvejic, Lloyd, & Vollmer-Conna, 2016;Krupp, Sliwinski, Masur, Friedberg, & Coyle, 1994;Short et al, 2002;Teodoro et al, 2018). Several explanations for these discrepancies have been proposed by different authors.…”
Section: The Relations Between Subjective and Objective Cognitive Finsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, our results support some previous studies that show discrepancies between subjective and objective cognitive measures in CFS (Cockshell & Mathias, 2014;Cvejic, Lloyd, & Vollmer-Conna, 2016;Krupp, Sliwinski, Masur, Friedberg, & Coyle, 1994;Short et al, 2002;Teodoro et al, 2018). Several explanations for these discrepancies have been proposed by different authors.…”
Section: The Relations Between Subjective and Objective Cognitive Finsupporting
confidence: 92%
“…Others have suggested that they overestimate their premorbid cognitive performance, like the "good-old-days" phenomenon (Sullivan & Edmed, 2012). The results also indicated that CFS might mimic functional cognitive disorder (FCD), i.e., a condition which has been suggested to have a subjective experience of cognitive dysfunction in the absence of underlying brain pathology Teodoro et al, 2018).…”
Section: The Relations Between Subjective and Objective Cognitive Finmentioning
confidence: 95%
“…This means that functional communication and swallowing disorders may go underdiagnosed and consequently under-reported. Currently, functional communication and swallowing disorders are a diagnosis of exclusion (De Letter et al 2012, Teodoro et al 2018, Kim et al 2018. Further research is needed to validate a set of positive diagnostic criteria for SLTs to use both within clinical and research practice.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high frequency of pain, including chronic migraine, fatigue and the subjective sense of "cognitive fog" in patients with FND [45][46][47]. Although distinct entities, there appears to be significant overlap with FND, fibromyalgia (FM) and chronic fatigue syndrome (CFS), particularly in the way patients describe subjective cognitive difficulties, perhaps underpinned by excessive attention towards the body, severe pain and fatigue [48]. It is necessary to recognize and treat these symptoms as part of FND, as they may be acting as either triggering or maintaining factors in FND.…”
Section: Comorbid Pain Fatigue and "Cognitive Fog"mentioning
confidence: 99%